Analysis of Protein O‐GlcNAcylation by Mass Spectrometry. (2nd February 2017) - Ma, Junfeng; Hart, Gerald W.
Abstract: O‐linked β‐D ‐ N ‐acetyl glucosamine (O‐GlcNAc) addition (O‐GlcNAcylation), a post‐translational modification of serine/threonine residues of proteins, is involved in diverse cellular metabolic and signaling pathways. Aberrant O‐GlcNAcylation underlies the initiation and progression of multiple chronic diseases including diabetes, cancer, and neurodegenerative diseases. Numerous methods have been developed for the analysis of protein O‐GlcNAcylation, but instead of discussing the classical biochemical techniques, this unit covers O‐GlcNAc characterization by combining several enrichment methods and mass spectrometry detection techniques [including collision‐induced dissociation (CID), higher energy collision dissociation (HCD), and electron transfer dissociation (ETD) mass spectrometry]. © 2017 by John Wiley & Sons, Inc.